Wybrane wskaźniki różnorodności biologicznej na tle cech utworów glebowych w wyżynnym borze jodłowym Abietetum albae - Lasota, Jarosław; Brożek, Stanisław; Błońska, Ewa; Wiecheć, Małgorzata (Leśne Prace Badawcze, 2017)
The aim of this study was to present the relationship between soil properties and biodiversity indexes in upland fir ( Abies alba ) forest associations ( Abietetum albae ). Our study was conducted in six areas representing the growth conditions of upland fir forests and the research plots were located in the Roztoczański and Świętokrzyski National Parks as well as Przedbórz, Radomsko, Piotrków and Janów Lubelski Forest District. On every plot, the topography was described, soil cores were examined and samples for laboratory analysis were taken. The following characteristics were determined for the soil samples: pH, C, N, Ca, Mg, Na and K content, particle size, exchangeable acidity, aluminum content and hydrolytic acidity. Additionally, enzyme activity in the soil samples (urease and dehydrogenase) was measured. In each test area, the stand characteristics were measured (diameter at breast height and height) floristic characteristics were described and the biodiversity indexes (Shannon, Simpson and Margalef indexes) were calculated. Different soil types (Gleysols, Brunic Arenosols, Gleyic Podzols and Hyperdistric Cambisols) were recorded for the investigated forest stands and the soils were categorized according to soil texture, C content, enzyme activity and different humus types (moder-mor, moder, moder-mull). The upland mixed coniferous forest sites were characterized by lower biodiversity indexes (2,6 Shannon index; 0,72 Simpson index; 4,9 Margalef index) while the upland mixed broadleaf forest sites showed higher indexes (3,3 Shannon index; 0,87 Simpson index; 9,4 Margalef index). The site index obtained for the fir stands confirmed these results.